THE PRACTICAL ROLE OF ARTIFICIAL INTELLIGENCE IN STRENGTHENING DIGITAL GOVERNANCE AND NETWORK SECURITY IN POST-CONFLICT AFGHANISTAN - Sadat, Mir Mohammad Naim; Esmati, Shahabuddin; Tokhi, Mustafa; Azizi, Muhammad Ajmal (Journal of Governance and Public Administration, 2025)
This study examines the practical role of artificial intelligence (AI) in strengthening digital governance and network security in post-conflict Afghanistan. Drawing on a qualitative approach, data were collected through semi-structured interviews with 20 key informants, including government officials, ICT and cybersecurity experts, academics, and representatives from international organizations, complemented by document analysis of policy reports and strategic frameworks. The findings reveal that AI is perceived as a critical enabler of governance reform, with the potential to enhance transparency, reduce corruption, and improve efficiency in service delivery, contributing to institutional legitimacy. At the same time, participants emphasized the importance of AI-driven cybersecurity tools, such as predictive analytics and anomaly detection, in mitigating rising digital threats from both state and non-state actors. However, the study also highlights significant barriers, including weak infrastructure, limited technical capacity, and reliance on external actors, which constrain effective adoption. These dual dynamics underscore that while AI offers opportunities for resilience and modernization, its success in fragile context depends on context-sensitive, ethically grounded, and inclusive deployment. The research contributes to ongoing debates on technology-enabled governance in fragile states and provides practical insights for policymakers, practitioners, and international partners engaged in Afghanistan's digital transformation